Intake of Vegetables and Fruits Through Young Adulthood Is Associated with Better Cognitive Function in Midlife in the US General Population. Issue 8 (4th June 2019) - Mao, Xuanxia; Chen, Cheng; Xun, Pengcheng; Daviglus, Martha L; Steffen, Lyn M; Jacobs, David R; Van Horn, Linda; Sidney, Stephen; Zhu, Na; Qin, Bo; He, Ka
ABSTRACT: Background: Vegetables and fruits (VF) may differentially affect cognitive functions, presumably due to their various nutrient contents, but evidence from epidemiologic studies is limited. Objectives: The aim of this study was to examine the long-term association between VF intakes, including VF subgroups, in young adulthood and cognitive function in midlife. Methods: A biracial cohort of 3231 men and women aged 18–30 y at baseline in 1985–1986 were followed up for 25 y in the Coronary Artery Risk Development in Young Adults Study. Diet was measured at baseline, and in examination years 7 and 20. Cognitive function was assessed at examination year 25 through the use of 3 tests: the Rey Auditory Verbal Learning Test (RAVLT), the Digit Symbol Substitution Test (DSST), and the Stroop test. The mean differences (MDs) with 95% CIs in cognitive scores across intake categories were estimated through the use of the multivariable-adjusted general linear regression model. Results: Excluding potatoes, intake of whole vegetables was significantly associated with a better cognitive performance after adjustment for potential confounders in all 3 cognitive tests (quintile 5 compared with quintile 1—RAVLT, MD: 0.33; 95% CI: 0.01, 0.64; P -trend = 0.08; DSST, MD: 2.84; 95% CI: 0.93, 4.75; P -trend < 0.01; Stroop test, MD: −2.87; 95% CI: −4.24, −1.50; P -trend < 0.01]. Similarly, intake of fruits, except fruit juices, was significantly related to a better cognitive performance (quintile 5 compared with quintile 1—DSST, MD: 2.41; 95% CI: 0.70, 4.12; P -trend = 0.03). Conclusions: This study supports the long-term benefits of VF consumption on cognitive performance, except those VF with relatively low fiber content such as potatoes and fruit juices, among the middle-aged US general population.